Combat drones - killing drones: A plea against flying robots - Marcel Dickow; Hilmar Linnenkamp (Stiftung Wissenschaft und Politik (SWP), 2013)
Medium altitude, long endurance drones are becoming a component of regular air forces. However, the extent to which manned aircraft are being replaced by such "MALE UAVs" (MALE = Medium Altitude, Long Endurance, UAV = Unmanned Aerial Vehicle) remains unclear. At present Germany is faced with determining with what means the Luftwaffe should be equipped in the medium term (up to 2020) and long-term (post-2020). Beyond military considerations, there are cooperation and industrial policy issues to be taken into account, since no one individual state in Europe can or wants to provide the financial means to develop a national MALE UAV model. Although European industry has already launched research and development projects, their governments are by no means on board. Likewise it is also unclear whether drones are to be armed in future. Discussion has been continuing for some time as to how far targeted killings are responsible and permissible. In contrast, no fundamental debate has so far taken place about what the ethical consequences are of the trend towards automated combat. Such a debate is now overdue and urgent, as the momentum of technological development conceals the danger that human beings may abdicate moral responsibility in decisions over the use of force
Keywords: 320